2022
DOI: 10.2478/hjbpa-2022-0008
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Workload and Career Development on Job Satisfaction; Case Study PT XYZ

Abstract: This research begins with the phenomenon of workload problems and unclear tasks that cause employees to feel the workload given by employees to get promotions in accordance with career development plans that have not been implemented properly. So that the resulting job satisfaction is not in accordance with the wishes of employees. The need of this investigation was to find out the relationship between work load (WL) and career development (CD) on job satisfaction (JS) for PT XYZ. This article use quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…ResultBased on the tables presented earlier, it can be seen that this study found that work environment and career development have a positive and significant influence on job satisfaction, which is in line with previous research conducted by(Jaskyte et al, 2010) and(Taheri et al, 2020) confirming that work environment has a positive influence on job satisfaction. Additionally, research by(Putra, 2020) and(Hayati et al, 2022) confirmed that career development has a direct and significant influence on job satisfaction. This study also found that job satisfaction has a positive and significant influence on employee retention, aligning with previous research by(Rahman et al, 2021) and(Sinaga & Sijabat, 2022) which confirmed that job satisfaction has a positive and significant influence on employee retention.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…ResultBased on the tables presented earlier, it can be seen that this study found that work environment and career development have a positive and significant influence on job satisfaction, which is in line with previous research conducted by(Jaskyte et al, 2010) and(Taheri et al, 2020) confirming that work environment has a positive influence on job satisfaction. Additionally, research by(Putra, 2020) and(Hayati et al, 2022) confirmed that career development has a direct and significant influence on job satisfaction. This study also found that job satisfaction has a positive and significant influence on employee retention, aligning with previous research by(Rahman et al, 2021) and(Sinaga & Sijabat, 2022) which confirmed that job satisfaction has a positive and significant influence on employee retention.…”
mentioning
confidence: 88%
“…Career development can be used as a measure to assess the level of job satisfaction in a company (Niati et al, 2021). Research (Hayati et al, 2022) It also mentions that career development affects job satisfaction. Based on these statements, the hypothesis can be formulated as follows:…”
Section: The Relationship Between Career Development and Job Satisfac...mentioning
confidence: 99%